Ta’ṡīru Kitāb al-Syāmil Fī Mahārāti al-Qirā’ah ladā al-Ṭulabi al-Mukaṡṡafi bi al-Jāmiʻah Al-Āmīn Al-Islāmiyyah Prenduan Sumenep Madura - Mahrus; Saiful Anam (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2023)
Both modern and Salafi Islamic boarding schools. Almost all boarding activities use the Arabic language, and every Islamic boarding school cannot be separated from learning the Yellow Book using the rules of grammar and morphology, all of which are inseparable from the Arabic language. To facilitate students' learning of the Arabic language, Kiahi Bastami Tebyan Master, wrote a book titled Kitab Al-Syamil. As a guide or an easy way for students to learn Arabic. This study investigates how learning the Book of Fasting affects reading skills of the Yellow Book. The purpose of this research is to find out the method of implementing the learning of the book Al-Syamil in reading the yellow book, and to know the factors of the extent of the effectiveness of the book Al-Samail in reading the yellow book. In this study using the quantitative research method, since this research is a type of quantitative research, the variables involved in this research are the X variable and the Y variable, for the X variable here, which is “the effect of learning a comprehensive book, while the Y variable is the ability to read the book As for the results of this study, the researchers found that there was an additional agenda for the students at the Institute of Al-Ameen Islamic University, which included learning about the basic rules of syntax and morphology.The first semester of the Idea Brendawan Institute.